Prediction of Successful Ovarian Protection Using Gonadotropin-Releasing Hormone Agonists During Chemotherapy in Young Estrogen Receptor-Negative Breast Cancer Patients - Lee, Dong-Yun; Kim, Ji-Yeon; Yu, Jonghan; Kim, Seok Won (Frontiers in Oncology, 2020)
Background: It is important to identify factors predicting successful ovarian protection using gonadotropin-releasing hormone agonists (GnRH) during chemotherapy. However, only few studies have prospectively accessed this issue in young breast cancer patients. Objective: This study evaluated the predictive factors for successful ovarian protection with GnRH agonists during chemotherapy in young estrogen receptor-negative breast cancer patients. Materials and Methods: This prospective study analyzed 67 estrogen receptor-negative breast cancer patients ≤ 40 years of age who were longitudinally assessed after receiving GnRH agonists during cyclophosphamide-based chemotherapy for ovarian protection. Associations between clinical characteristics or pretreatment hormones and successful ovarian protection (resumption of menstruation and anti-Müllerian hormone (AMH) ≥ 1 ng/mL). Results: The mean age and pretreatment serum level of AMH were 33.2 years and 4.57 ng/mL, respectively. At 12 months after the completion of chemotherapy, most women (97%) experienced the resumption of menstruation. However, the proportion of patients with AMH ≥ 1 ng/mL at 12 months was 70.1%. In multivariate analyses, only the pretreatment serum AMH level (P<0.001) was predictive for AMH ≥ 1 ng/ml at 12 months. Receiver-operator characteristics curve analyses of pretreatment AMH exhibited an area under the curve of 0.866 (95% CI 0.777–0.955) for AMH ≥ 1 ng/ml at 12 months. The cut-off value for the prediction of AMH concentration ≥ 1 ng/ml at 12 months was 2.87 ng/ml of pretreatment AMH with a sensitivity of 0.87 and specificity of 0.75. Conclusions: Pretreatment AMH (2.87 ng/ml) is a useful predictor for AMH ≥ 1 ng/ml at 12 months after receiving GnRH agonists in young estrogen receptor-negative breast cancer patients. This finding can help improve decision-making regarding fertility preservation.